Um estudo sobre o desenvolvimento instrumental da cozinha paulista, na primeira metade do século XX - Lima, Lucia Helena Soares de (2016)
This research aims to understand the process of transformation of paulista cuisine, by examining the instruments used in food preparation in the city of São Paulo during the first half of the 20th century. The analysis of documents in the periodicals of the time, such as advertisements and articles on city subjects, books written, and surveys conducted during this period, enabled the perception of how new urban problems such as disease and collective living spaces interfered in the domestic space and in eating habits, and influenced research in the health arena as well as the adoption of hygiene policies. This analysis also made it possible to verify that while the adoption of modern kitchen tools and new dishes was incorporated by the most economically favored segment, the lack of support from public policies and the financial difficulties of much of the population determined the delay in the acquisition of the gas stove, despite the advance of industrialization and the growth of the economy